Optimization of emulsion polymerization of styrene and methyl methacrylate (MMA) - Yok, Loke Kam (2013)
This paper studies the optimization of emulsion copolymerization of Styrene and Methyl Methacrylate (MMA). A model-based framework for optimal operation of copolymerization processes was used in gPROMS environment and enables us to predict the maximum monomer conversion for a given total monomer feed over the batch time. The complexities of the process were represented by mathematical models for optimization and control. A process model involving the equations for mass and energy balance describing the particle evolution in a batch reactor and diffusion controlled kinetics is incorporated into the optimization framework. The modeling is account for complex physic-chemical sub-processes involving particle formation mechanisms with two monomer droplets, surfactants, initiator and particulates. Using gPROMS, the system analyzed the data, created models, developed algorithms, manipulated and plotted based on the functions and data. The determination of optimal profile for control variables used for emulsion polymerization of styrene and MMA that yielded desired conversion with fixed batch time and fixed number average molecular weight in batch reactor respectively were carried out in batch reactor. Reduction of the pre-batch time increases the Mn but decreases the conversion (Xn). The faster the addition of monomer into the reactor, the earlier the growth of the polymer chain leading to higher Mn. The increases of the reaction temperature will decrease the Mn since increases of temperature will increase the rate of termination reaction.